(untitled) (Research, Society and Development, 2022)
Introduction: Processed foods, such as ultra-processed ones, are foods with high energy density, which can increase caloric intake in people’s diets. These foods are associated with increased intake of non-oil foods, which can lead to obesity, diabetes, hypertension, and other chronic communicable diseases. Objective: to investigate the factors that do not intend to consume ultra-processed foods through complementary feeding. Methodology: this is a literature review, The bibliographic review was carried out through journals, books, e-books and scientific digital research: Scientific Electronic Library Online: (Scielo), Bireme (Latin American and scientific digital search) Caribbean Health Sciences Information Portal, CAPES Periodicals Portal, Virtual Health Library (VHL). Results and Discussion: Discussion: Nutrition in the first years of growth and development of life: an important role in children’s growth. The World Health Organization (WHO) and recommends the Ministry of Exclusive Milk until birth, the Ministry of Health of Health (WHO) the 6th month of exclusive birth, the Ministry of Health until birth, additional health care from birth to newborn illnesses and prevention. Conclusion. The supply of non-reduced foods is considered an indication of sufficient complementary feeding in infants, a factor in stopping the duration and frequency of breastfeeding, formation of habits and tendencies towards obesity and the development of chronic non-communicable diseases in adult life.